(untitled) (European Journal of Language and Literature, 2015)
The usage of social media by Kosovar politicians is almost absolute. Politicians of all levels have their accounts on Facebook as well as other social networks. They use those for various reasons, starting from contacting the voters and supporters during the election campaigns as well as during the time they are in the office, up to presenting their stands and ideas that have do with different issues of public interest. For many of them, especially for low-level politicians the social media, mainly Facebook, have become the only place where they express themselves, since they find it almost impossible to become a part of the traditional media, especially of those on the national level, like newspapers, radio or television. Whereas for high-leveled politicians, concretely the heads of main institutions like the prime-minister, the head of parliament or the president, who refuse to be interviewed and be present in political shows where they could face questions from the journalists or the public, they are using Facebook statements in order to avoid direct questions from the journalists about the political subjects of the day. By making it impossible for them to take direct answers through their journalists the traditional media (newspapers, radio, TV) have to quote the posts that the politicians are making on Facebook. The kosovar journalists and the heads of media see this tendency of politicians, especially of the prime minister as the lack of transparency, avoidance of accountability, control of information and setting the agenda of the media. This paper attempts to argument the hypothesis that the high level politicians, the heads of main state institutions in Kosovo are controlling the information in traditional media through the usage of social media. In order to argument this hypothesis as a case study we have taken the Kosovar (ex)PM Hashim Thaçi whose almost every status and update has been quoted by the media. We have also interviewed journalists and editors of Kosovar media houses who have expressed their thoughts about the subject, while supporting the hypothesis of this paper.